Density, viscosity, physical solubility and diffusivity of CO 2 in aqueous MDEA+bmimBF 4 solutions from 303 to 333K - Ahmady, A.; Hashim, M.A.; Aroua, M.K. (Elsevier, 2011)
In this study, the physical solubility and diffusivity of N 2O in aqueous MDEA+bmimBF 4 solutions were measured over a range of temperatures of 303-333K and bmimBF 4 concentrations of 0-2.0molL -1 at atmospheric pressure. The total MDEA concentration in the solutions was kept constant at 4molL -1. The " N 2O analogy" was then used to estimate the physical solubility and diffusivity of CO 2 in aqueous MDEA+bmimBF 4 solutions. The density and viscosity of aqueous MDEA+bmimBF 4 solutions were also measured over the same range of temperatures and concentrations of the ionic liquid. These data were used to develop correlations for the prediction of CO 2 diffusivity in these systems.